RUVBL1 is an amplified epigenetic factor promoting proliferation and inhibiting differentiation program in head and neck squamous cancers. (December 2020) - Lin, Derrick; Lin, Brian; Bhanot, Haymanti; Riou, Rozenn; Abt, Nicholas B.; Rajagopal, Jayaraj; Saladi, Srinivas Vinod
Highlights: RUVBL1, an epigenetic factor and p63 interacting partner, is amplified and overexpressed in head and neck cancers. H2AZ, deposited by RUVBL1 onto chromatin, is overexpressed, and inversely correlates to differentiation program in HNSCC. Single cell analysis reveals low expression of differentiation program in HNSCC. RUVBL1 and H2AZ promote proliferation and regulate transcription of differentiation genes in HNSCC cells. Abstract: Mutations in histone modifying enzymes and histone variants were identified in multiple cancers in The Cancer Genome Atlas (TCGA) studies. However, very little progress and understanding has been made in identifying the contribution of epigenetic factors in head and neck squamous cell carcinoma (HNSCC). Here, we report the identification of RUVBL1 (TIP49a), a component of the TIP60 histone modifying complex as being amplified and overexpressed in HNSCC. RUVBL1 plays a key role in incorporating histone variant H2AZ in chromatin thereby regulating transcription of key genes involved in differentiation, cancer cell proliferation and invasion. H2AZ is also overexpressed in HNSCC tumors thereby regulating RUVBL1/H2AZ dependent transcriptional programs. Patient data analysis of multiple cohorts including TCGA and single cell HNSCC data indicated RUVBL1 overexpression as a poor prognostic marker and predicts poor survival. In vitro experiments indicate a pro-proliferative role for RUVBL1/H2AZ in HNSCC cells. RUVBL1 inversely correlates with differentiation program and positively correlates with oncogenic programs, making it a key contributor to tumorigenesis and a vulnerable therapeutic target in HNSCC patients.